Efficiency Assessment and Ranking of TUMS Hospitals Using Data Envelopment Analysis - Mohammad Khodabakhshi; Hossein Dargahi; Hajar Moammai (Tehran University of Medical Sciences, 2017)
Background and Aim: Because human health is a strategic priority for all communities, investing in this sector will be very important. The purpose of this research is to evaluate the efficacy of hospitals affiliated to Tehran University of Medical Sciences from 2013 to 2015 and their ranking, and provide a perspective for dynamic managers in this area. Materials and Methods: This is an applied study, and in terms of nature, it is descriptive. The statistical population of this study was 13 hospitals of this university. In this research, the efficacy of hospitals during the years 2013 to 2015 through the data envelopment analysis and Output-based method was evaluated. By carefully examining global research, input and output indicators were identified. Input indexes were the number of beds and the number of doctors (general, residents and specialists); and output indexes were the total days of hospitalization, the number of outpatients, and the number of bed-days. Results: According to the study model, university hospitals with high efficiency to low efficiency are as follows: Arash, Bahrami, Zanan, Roozbeh, Amiralam, Ziaeeyan, Baharlou, Razi, Valiasr, Sina, Farabi, Imam Khomeini and Shariati hospitals. Conclusion: According to output-based method, by calculating the efficiency mean of hospitals during the years 2013 to 2015; Arash hospital, Bahrami hospital and Zanan hospital are determined to be the most efficient; and, Farabi hospital, Imam Khomeini hospital, and Shariati hospital are the ones with the lowest efficiency.